THERAPY OF INFLAMMATORY COLONOPATHY IN CHILDREN - E.N. Fedulova (Union of pediatricians of Russia, 2008)
The problem of non specific ulcer colitis is one of the most complicated ones in modern gastroenterology, especially in pediatric practice. This is due to the fact that despite successes in studying the pathogenesis of the disease and creation of anti inflammatory medications of the new generation, in the past quarter of the century the incidence of ulcer colitis has increased at 8-14 times. Besides, the incidence of pathological process formation in the infancy has increased at 1,5 times, heavier extraenteric manifestations appeared, development of resistence to traditional therapy is observed more often, early incapacitation of patients, which needs developing new methods of treatment.Key words: non specific ulcer colitis, crohn's disease, therapy, children.